An investigation of the relationship between arterial aortic stiffness and coronary slow flow that was detected during coronary angiography. Issue 4 (2nd April 2020) - Genc Tapar, Gulsen; Elcik, Deniz; Dogan, Ali; Altunel, Ebru; Inanc, Mehmet Tugrul; Alcali, Bilal; Boylug, Sibel; Oguzhan, Abdurrahman; Topsakal, Ramazan; Ergin, Ali; Kalay, Nihat
Abstract: Aim: Increased intimal thickness in coronary arteries, extensive calcification, and atheromatous plaque that does not cause luminal irregularities in a significant portion of the patients with coronary slow flow (CSF). Arterial stiffness is an indicator for atherosclerosis. We aimed to investigate the relation between coronary slow flow phenomenon (CSFP) and arterial stiffness. Method: Total of 73 patients were included in the study, and a control group was formed with 64 individuals. Aortic stiffness index β (ASIβ) and pulse wave velocity (PWV) were used as the determinant of arterial stiffness in all analyses. Result: Pulse wave velocity values were significantly higher in the coronary slow flow group than the control group ( P  < .001). PWV, aortic stiffness index β (ASIβ) values were found to be significantly higher in the CSF group. ASIβ value was 3.4 ± 1.0 in CSF patients and 2.2 ± 0.6 in the control group ( P  < .001). Receiver operating characteristic curve (ROC) analysis showed that PWV predicted coronary slow flow with 97% sensitivity and 90% specificity for 7.15 cutoff value. And aortic stiffness index was found to predict coronary slow flow with 83% sensitivity and 75% specificity for 2.63 cutoff value. Conclusion: Our findings prove that coronary slow flow phenomenon should be considered a subgroup of coronary artery diseases and that increased PWV is an indicator of CSFP.